Fotobiomodulação associada à bandagem elástica no tratamento de complicações de ferida operatória de mulheres com câncer de mama - Kemerich, Jhulie Anne Pinheiro (2024)
Among the forms of treatment for breast cancer, surgical procedures stand out. However, cancer patients are susceptible to conditions that interfere with the healing process and that can lead to surgical wound complications. Photobiomodulation (PBM) is a therapeutic alternative that stimulates re-epithelialization and retraction of the lesion. In addition, elastic bandages can be used to reduce tension on the surgical wound in order to bring the edges closer together, favoring tissue regeneration. This study aims to verify the effectiveness of a photobiomodulation protocol and functional elastic bandage on surgical wound complications in patients undergoing surgery for breast cancer. The study included women following surgery for breast cancer who developed scar complications such as necrosis and dehiscence. Wound characteristics were assessed using the Bates-Jensen Wound Assessment Tool, together with a complementary form. The wound area was analyzed using Image J® software. The PBM protocol was carried out with a cluster that has a central laser point at a wavelength of 660 nm and, around it, four 658 nm LED points and four 858 nm LED points, with a total power of 0.41 W per area of irradiation. The dose used was 4 J/cm², twice a week, for 7 weeks. The elastic bandage was applied with a cut of sufficient size to promote support and bring the tissue closer to the surgical wound. 12 patients participated in this study. As a result, it was possible to observe a significant reduction in the area of the lesion after the treatment protocol (p<0.001), in addition to improvements in the general condition of the wound (p = 0.007). Thus, PBM associated with functional elastic bandage demonstrates its potential therapeutic effect on healing complications resulting from surgery to treat breast cancer.